Solar activity over nine millennia: A consistent multi-proxy reconstruction - Wu, C.; Usoskin, I.; Krivova, N.; Kovaltsov, G.; Baroni, M.; Bard, E.; Solanki, S. (Astronomy & Astrophysics, 2018)
International audience Aims. The solar activity in the past millennia can only be reconstructed from cosmogenic radionuclide proxy records in terrestrial archives. However, because of the diversity of the proxy archives, it is difficult to build a homogeneous reconstruction. All previous studies were based on individual, sometimes statistically averaged, proxy datasets. Here we aim to provide a new consistent multi-proxy reconstruction of the solar activity over the last 9000 yr, using all available long-span datasets of 10 Be and 14 C in terrestrial archives. Methods. A new method, based on a Bayesian approach, was applied for the first time to solar activity reconstruction. A Monte Carlo search (using the χ 2 statistic) for the most probable value of the modulation potential was performed to match data from different datasets for a given time. This provides a straightforward estimate of the related uncertainties. We used six 10 Be series of different lengths (from 500-10 000 yr) from Greenland and Antarctica, and the global 14 C production series. The 10 Be series were resampled to match wiggles related to the grand minima in the 14 C reference dataset. The stability of the long data series was tested. Results. The Greenland Ice-core Project (GRIP) and the Antarctic EDML (EPICA Dronning Maud Land) 10 Be series diverge from each other during the second half of the Holocene, while the 14 C series lies in between them. A likely reason for the discrepancy is the insufficiently precise beryllium transport and deposition model for Greenland, which leads to an undercorrection of the GRIP series for the geomagnetic shielding effect. A slow 6-7 millennia variability with lows at ca. 5500 BC and 1500 AD in the long-term evolution of solar activity is found. Two components of solar activity can be statistically distinguished: the main component, corresponding to the "normal" moderate level, and a component corresponding to grand minima. A possible existence of a component representing grand maxima is indicated, but it ...